2017
DOI: 10.1142/s021827181750153x
|View full text |Cite
|
Sign up to set email alerts
|

Particles on the rotating channels in the wormhole metrics

Abstract: In the Ellis-Bronnikov wormhole (WH) metrics the motion of a particle along curved rotating channels is studied. By taking into account a prescribed shape of a trajectory we derive the reduced $1+1$ metrics, obtain the corresponding Langrangian of a free particle and analytically and numerically solve the corresponding equations of motion. We have shown that if the channels are twisted and lag behind rotation, under certain conditions beads might asymptotically reach infinity, leaving the WH, which is not poss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Therefore, it was argued [9] that CDOs could indeed be amply efficient to account for the TeV blazar emission. For the wide range of cases, ICS remains the dominant factor in limiting the maximum Lorentz factor of accelerated particles, letting them produce very high-energy photons [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] TeV. Obviously, an important restriction of the [9] approach is that only straight magnetic field lines were considered, whereas, in realistic astrophysical situations, the magnetic field lines are curved.…”
Section: Acceleration Of Particles By Rotating Magnetospheres In Agnmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was argued [9] that CDOs could indeed be amply efficient to account for the TeV blazar emission. For the wide range of cases, ICS remains the dominant factor in limiting the maximum Lorentz factor of accelerated particles, letting them produce very high-energy photons [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] TeV. Obviously, an important restriction of the [9] approach is that only straight magnetic field lines were considered, whereas, in realistic astrophysical situations, the magnetic field lines are curved.…”
Section: Acceleration Of Particles By Rotating Magnetospheres In Agnmentioning
confidence: 99%
“…The possible importance of this result in the context of centrifugally driven dynamics of particles in rapidly rotating pulsar magnetospheres and astrophysical jets was later repeatedly pointed out [7] and extensively studied in a number of subsequent publications [8][9][10][11][12]. Namely, particle acceleration by rotating magnetospheres in active galactic nuclei was investigated [13]; the role of radiation reaction forces in the dynamics of centrifugally accelerated particles was explored [14]; centrifugal acceleration was studied in isotropic photon fields [15] and in wormhole metrics [16].…”
Section: Introductionmentioning
confidence: 99%
“…From Eq. ( 6) one can straightforwardly show that the radial velocity behaves with r as follows (Arsenadze & Osmanov 2017)…”
Section: Main Approachmentioning
confidence: 99%
“…In general it is believed that WHs can provide magnetic fields as strong as 10 13 G [8], which means that if the charged particles are trapped by rotating magnetic field lines, dynamics might reveal interesting features. A single particle approach has been proposed in the work [9], where by implying the method developed in [10,11] it has been shown that if the magnetic field lines are twisted and are lagged behind the rotation, in certain cases, particles can leave the WH region.…”
Section: Introductionmentioning
confidence: 99%